JURIDICAL REVIEW AGAINST INCUMBENTS LEAVE IN LAW NUMBER 10 OF 2016 ON THE ELECTION OF THE GOVERNOR, REGENT, AND MAYOR - Wardani Amnesti, Sheila Kusuma (Fakultas Hukum Universitas Muhammadiyah Magelang, 2018)
Regional head elections held simultaneously on a regular basis in five years held in several regions by the mandate of Law Number 10 of 2016 still leave some problems. These problems include pre-post-conflict local elections when post-conflict local elections and post-conflict local elections. If some of these problems are described, one of them is the problem before the post-conflict local election process, namely the issue of incumbent leave. Regarding the arrangement of incumbent leave, there is still controversy. This has a significant impact on the holding of regional head elections. Some regional heads who are running for re-election in the following period (incumbent) object to the obligation of leaves contained in Article 70 paragraph (3) of Law Number 10 of 2016. However, on the other hand, many things must be considered to maintain the contents of Article 70 paragraph (3) regarding the obligation of incumbent leave. The research is descriptive analytical, namely making a precise, factual enunciation and accurately dealing with the facts. This research is a normative juridical approach with the Law approach (Concept approach) and conceptual approach (Conceptual Approach). Obligations regarding incumbent leave are mandatory for incumbents when nominating themselves again in the next period, although in some other laws and regulations governing voluntary consent of absence rules.